1999
DOI: 10.1161/01.str.30.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Brain Morphology for the Men of the NHLBI Twin Study

Abstract: Background and Purpose-Cross-sectional studies show that cerebrovascular risk factors are associated with increased brain atrophy, accumulation of abnormal cerebral white matter signals, and clinically silent stroke. We extend these findings by examining the relationship between midlife cerebrovascular risk factors and later-life differences in brain atrophy, amount of abnormal white matter, and stroke on MRI. Methods-Subjects were the 414 surviving members of the prospective National Heart, Lung, and Blood In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
198
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(207 citation statements)
references
References 58 publications
5
198
0
Order By: Relevance
“…17 The presence or absence of brain infarction was determined from the size, location, and imaging characteristics of the lesion. 18 SBI was defined as a cavitation on the fluidattenuated inversion recovery sequence of at least 3 mm in size, and distinct from a vessel due to the lack of signal void on T2 sequence, and of equal intensity to CSF. In a pilot reliability study, a total of 15 MRIs were read by 2 physicians to classify SBI (C.S.D., M.Y.).…”
Section: Mrimentioning
confidence: 99%
“…17 The presence or absence of brain infarction was determined from the size, location, and imaging characteristics of the lesion. 18 SBI was defined as a cavitation on the fluidattenuated inversion recovery sequence of at least 3 mm in size, and distinct from a vessel due to the lack of signal void on T2 sequence, and of equal intensity to CSF. In a pilot reliability study, a total of 15 MRIs were read by 2 physicians to classify SBI (C.S.D., M.Y.).…”
Section: Mrimentioning
confidence: 99%
“…Yet, to date few studies have examined the simultaneous relationships among cardiac output, blood pressure, and systemic hemodynamic function and measures of brain function and structure. Past studies have investigated these relationships primarily by examining the prevalence of specific risk factors in an epidemiological context (Claus et al, 1996;DeCarli et al, 1999;de Leeuw et al, 2004;Vermeer et al, 2003). Most elderly people with cardiovascular disease have a variety of underlying risk and etiological factors (Martins e Silva & Saldanha, 2007;Terry et al, 2005;Tranche, Galgo, Mundet, & Sanchez-Zamorano, 2005).…”
mentioning
confidence: 99%
“…The cerebral atrophy refers to a decrease of the brain in weight and/or volume ;or still in an increase in the difference between the volume of the brain and the ability cranial, including the volume of the cerebrospinal fluid [1].Several studies found that the age is associated with the cerebral atrophy [1][2][3][4].In effect, it is known that a high blood pressure increases the risk of vascular lesions in the brain [5][6][7].The obviousness of the relationship between blood pressure and cerebral atrophy is less clear but some studies reveal that a high blood pressure during the period of the average age of the life (midlife) drives to cerebral atrophy later [8][9]. In our environment, there is no data relating to the cerebral atrophy.…”
Section: Introductionmentioning
confidence: 99%